THE MANAGEMENT OF COMMERCIAL APARTMENT IN THE PERSPECTIVE OF UNIT OWNERS’ PROSPERITY IN INDONESIA (Case Study in Apartemen Pondok Indah Villa III Jakarta and Apartemen Sejahtera Yogyakarta, Indonesia) : Maria Hutapea, 2024 Volume 2024, pp. 47-52 - Hutapea, Maria (MATTER: International Journal of Science and Technology, 2024)
The purpose of the research is to find out the managemenrt of commercial apartment relating to the prosperity of the unit owners. It uses empirical legal research by examining the operation of management of the apartment by case study at Apartemen Pondok Klub Villa III Jakarta and Apartemen Sejahtera Yogyakarta, in the perpective of the prosperity of the unit owners. The result shows that both apartment management embody the prosperity of the unit owners eventhough with different management and result. In the cases, the Apartemen Pondok Klub Villa III Jakarta is managed by association body of owners, while Apartemen Sejahtera Yogyakarta is managed by a company established by the committee of association body of owners. These different management results different benefit to the unit owners of the apartement.